PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA MATA PELAJARAN MENGAPLIKASIKAN ADMINISTRASI PERKANTORAN DI TEMPAT KERJA UNTUK MENINGKATKAN KEAKTIFAN SISWA - Windandari, Sakti (Pendidikan Administrasi Perkantoran FKIP Univesitas Sebelas Maret, 2013)
The purpose of this research was to know whether the application of cooperative learning jigsaw type in applying office administration at work place lesson could improve the student active involvement of class XII C office administration skill program of SMK Wikarya Karanganyar In The Academic Year 2011/2012. The type of the research done by the researcher was clasroom action research which was carried out in two cycles where each cycle was carried out in four steps, theywere: (1) planning, (2) implementation, (3) observation, and (4) reflection. The subject of this research was 36 students of class XII C Office Administration Skill Program of SMK Wikarya Karanganyar in academic year 2011/2012. The technique of collecting data was done through the following activities they are: (a) observation, (b) interview, (c) test, and (d) documentation. Based on this research, it can be concluded that the application of cooperative learning jigsaw type in applying office administration at work place lesson can improve the student active involvement class XII C office administration skill program of SMK Wikarya Karanganyar in the academic year 2011/2012. That was reflected in the following indicators: (1) the improvement of the student active involvement by 19,45% (from 80,55% at cycle I became 100% at cycle II), (2) the improvement of the student active involvement in asking question by 16,67% (from 66,66% at cycle I became 83,33% at cycle II), (3) the improvement of the student active involvement in discussion by 16,66% (from 72,22% at cycle I became 88,88% at cycle II), (4) the improvement of the learning result achievement by 13,89% (from 86,11% at cycle I became 100% at cycle II).Key words: Cooperative Learning Jigsaw Type, Student Active.